Magnetic resonance imaging-guided disc–condyle relationship adjustment via articulation: a technical note and case series - Xiong, Xin; Yin, Xiaoli; Liu, Fang; Qin, Danqing; Liu, Yang (Journal of international medical research, 2020)
A normal disc–condyle relationship is crucial to the health and function of the temporomandibular joint. We herein introduce a novel technique that can precisely and rapidly restore the disc–condyle relationship. An initial bite rim was made, and the patient was instructed to wear this bite rim during magnetic resonance imaging (MRI) scanning. A quick MRI scan was performed, and the disc–condyle relationship and direction and vector of the displacement was measured. Adjustments to the mandible position were made on an articulator based on the measurements, after which a second bite rim was made. A second quick preview MRI scan was immediately performed, and the images were evaluated and measured again. Additional adjustments were made as needed, and the preview scan was repeated until an ideal disc–condyle relationship was achieved. Once a good disc–condyle relationship was acquired, the mandible position was recorded as the treatment mandible position, and a splint was fabricated. MRI visualization enabled precise and very fine adjustment of the disc–condyle relationship by articulating. This technique might help to simplify the clinical process and improve treatment effectiveness.